Variations of salivary cortisol in dogs exposed to different cognitive and physical activities. Issue 4 (2nd October 2018) - Colussi, Alice; Stefanon, Bruno; Adorini, Chiara; Sandri, Misa
Abstract: Working dogs are gaining popularity for their ability to learn and perform tasks entertaining their human companions. For this reason, dogs are often subjected to various stimuli due to inter- and intra-specific interactions, environmental variations and effort required by different activities. In the present study, salivary cortisol was measured to monitor physiological response to different conditions. The first study was performed to assess the variability of salivary cortisol in dogs in usual environmental conditions. For this, salivary cortisol was measured in 10 dogs at home during three not consecutive days at three different times of the day and not significant variations between days and time of sampling were observed. In the second study, salivary cortisol was measured in dogs before and after Pointing Hunting (No. 5), Tracking for Ungulate Hunting (No. 6), Blood Tracking (No. 4), Agility Training (No. 6) and Animal Assisted Activities (AAA, No. 6). Salivary cortisol concentration significantly increased after the Pointing Hunting activity ( p  < .05), while salivary cortisol significantly decreased at the end of AAA session ( p  < .05). No significant differences in cortisol variations were observed for Tracking for Ungulate Hunting, Blood Tracking and Agility Training, before and after the activities. The response of cortisol suggests that the extent of hypothalamus–pituitary–adrenal axis activation varies between short high-intensity activities and endurance exercises. The measurement of salivary cortisol can support the trainers to evaluate the animal response to the stimulations.